Decreased GLUT2 and glucose uptake contribute to insulin secretion defects in MODY3/HNF1A hiPSC-derived mutant β cells - Blaise Su Jun Low (Nature Portfolio, 2021)
Heterozygous HNF1A mutations can give rise to maturity onset diabetes of the young 3 (MODY3), characterized by insulin secretion defects. Here the authors show that MODY3-related HNF1A mutation in patient hiPSCderived pancreatic cells decreases glucose transporter GLUT2 expression due to compromised DNA binding.